Levantamento do potencial energético solar da ilha do Marajó utilizando sistema de informação geográfica e dimensionamento de um sistema fotovoltaico isolado de pequeno porte - TELES, Mailson Borges (2024)
Through this work the thematic maps were drawn, representing the direct, diffuse and global solar irradiation for the Marajó archipelago, in order to show the feasibility of generating electricity through solar renewable source and identify which areas have the highest potential, as well propose the basic design of an isolated photovoltaic system for a typical residence in the region. For this, the concepts of solar energy in order to understand the main features of this abundant renewable resource were discussed, as well as seek to know how solar radiation can be transformed into electrical energy by means of photovoltaic cells. To obtain the thematic maps was necessary to seek the understanding and mastery of geographic information systems - GIS. The tool that has proved very useful in presenting information that assist in the decision making process. Then we will introduce a proposed photovoltaic system isolated small for the care of a residence located in a region that, according to the solarimetric maps, shows good potential of solar energy to be converted into electrical energy. The maps produced in chapter 3 show that the solar radiation on the island between 4.5 kWh/m2 /day getting to reach 6.2 kWh/m2 /day. Therefore, it is envisioned that the Marajó island has a good potential for the generation of electricity through renewable solar power.